ChemInform Abstract: Synthesis of Functional ′Polyolefins′: State of the Art and Remaining Challenges. Issue 37 (22nd August 2013) - Franssen, Nicole M. G.; Reek, Joost N. H.; de Bruin, Bas
Abstract Review: 279 refs.